The Struggle for Recognition: Embracing the Islamic Welfare Effort in Indonesian Welfare System - Abbas, Sirojudin (Studia Islamika, 2005)
This article traces the struggle of Indonesian Muslims to integrate Islam welfare programs into the statutory social welfare policy and provisions in Indonesia. Indonesia Muslims have gone through a long process of political struggle and negotiation to be able to embrace religious based social welfare programs as one element of a pluralistic social welfare system. The enactment of Law number 38/1999 on zakat administration and its utilization of Islamic welfare purposes signifies the formal accomodation of Islamic welfare effort into social welfare policies in Indonesia.DOI: 10.15408/sdi.v12i1.645